2012
DOI: 10.1089/ten.tea.2011.0430
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous Collagen Nerve Conduits for Spinal Cord Repair

Abstract: Nerve regeneration in an injured spinal cord is often restricted, contributing to the devastating outcome of neurologic impairment below the site of injury. Although implantation of tissue-engineered scaffolds has evolved as a potential treatment method, the outcomes remain sub-optimal. One possible reason may be the lack of topographical signals from these constructs to provide contact guidance to invading cells or regrowing axons. Nanofibers mimic the natural extracellular matrix architecturally and may ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 54 publications
2
105
1
Order By: Relevance
“…Further translational applications can extend to the choice of different materials for specific applications. In terms of direct scaffold implantation, both our and others’ studies have already demonstrated that electrospun scaffolds can be directly implanted into the spinal cord for SCI treatment [24,25]. As for applications where cell harvesting is required, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further translational applications can extend to the choice of different materials for specific applications. In terms of direct scaffold implantation, both our and others’ studies have already demonstrated that electrospun scaffolds can be directly implanted into the spinal cord for SCI treatment [24,25]. As for applications where cell harvesting is required, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The focus was initially directed to neuronal cells [7,9,11] but more recent studies are contributing to shed some light on the effect of this parameter on other CNS cellular key players, such as astrocytes [14 -17]. It is known that microglia, the immune cells of the CNS, play a critical role in CNS homeostasis as well as being in the frontline of the tissue response to injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…Under the scope of the development of scaffolds for CNS tissue engineering, neurons have been under the spotlight, so far. It has been shown that fibrous surfaces support axonal guidance and growth [7][8][9], as well as stemcell differentiation into the neuronal lineage [10,11]. The number of studies investigating the influence of surface features on glial cells is increasing, yet focused on astrocytes, mainly due to astrocytes' key role in the formation of the glial scar in response to an injury to the CNS [12].…”
Section: Introductionmentioning
confidence: 99%
“…Within SCI models, self-assembling IKVAV peptide amphiphile nanofibers promote functional recovery and axon elongation following SCI [9]. Furthermore, fibrous fibronectin channels [10], aligned channels filled with self-assembling peptide nanofibers [11], collagen nanofibers [12], and aligned poly-L-lactic acid (PLLA) microfibers [13] stimulate axonal migration into the biomaterial scaffold.…”
Section: Introductionmentioning
confidence: 99%